(3GdHjGf aj Gdabgs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3MSjf Hf fXGe GdOjfs)
(3ChdgG (B:s
(3GdMeO ddg(B...(3CeG HYO aEf GdCOdI GdYbdjI hGdfbdjI eJWGHbI Ydi TQa GdYdhe hef CgegG eYQaI TQY GdMj Gdbjhe(B...s
(3BNQgG (B:s
(3gPG Hjf Cf GdUhe efbhd ef eYfGg GddZhj adG jdRe GdYGej eYQaI Pdc dYSQg Hd gh ef aQV GdYdeGA(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B109s
(3GdPQjYI(B:(3L(B3(3,U(B167(3,Qbe(B621s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis